PEGylated Terbium-Based Nanorods as Multimodal Bioimaging Contrast Agents - Caro Salazar, Carlos; Páez-Muñoz, José M.; Beltrán, Ana M.; Pernia Leal, Manuel; García-Martín, María Luisa (ACS, 2021)
Diagnostic imaging strongly relies on the use of contrast agents (CAs). In general terms, current CAs present undesirable side effects that encourage researchers and pharmaceutical companies to continually search for safer and more versatile alternatives. Here, we describe the synthesis and characterization of terbium-based nanorods (TbNRs) as a potential alternative to traditional CAs for magnetic resonance imaging (MRI) and X-ray computed tomography (CT). The paramagnetism and high atomic number of Tb provide TbNRs with both magnetic relaxivity and X-ray attenuation capabilities. After surface functionalization with a polyethylene glycol (PEG)-derived ligand, TbNRs showed high colloidal stability in physiological media. Additionally, toxicity studies conducted in cell cultures and zebrafish embryos demonstrated the safety of the as-synthesized TbNRs, thus supporting their potential use as CAs. Lastly, in vivo imaging experiments in mice demonstrated that TbNRs produce remarkable contrast enhancement on both MRI and CT.
Keywords: Anatomía; Ligandos; Ligands; Anatomy; X-rays; Biological imaging; Magnetic resonance imaging